Spin singlet formation in MgTi2O4: evidence of a helical dimerization pattern. - Schmidt, M; Ratcliff, W; Radaelli, P; Refson, K; Harrison, N; Cheong, S (2004)
The transition-metal spinel MgTi2O4 undergoes a metal-insulator (M-I) transition on cooling below T(M-I)=260 K. A sharp reduction of the magnetic susceptibility below T(M-I) suggests the onset of a magnetic singlet state. Using high-resolution synchrotron and neutron powder diffraction, we have solved the low-temperature crystal structure of MgTi2O4, which is found to contain dimers with short Ti-Ti distances (the locations of the spin singlets) alternating with long bonds to form helices. Band structure calculations based on hybrid exchange density functional theory show that, at low temperatures, MgTi2O4 is an orbitally ordered band insulator.